The Islamists are not coming - KURZMAN, Charles (Institutional Knowledge at Singapore Management University, 2010)
Do Muslims automatically vote Islamic? That's the concern conjured up by strongmen from Tunis to Tashkent, and plenty of Western experts agree. They point to the political victories of Islamc parties in Egypt, Palestine, and Turkey in recent years and warn that more elections across the Islamic world could turn power over to anti-democratic fundamentalists.